Mastering the technique of taking a rebound on opponent's shield by basketball players of initial level of specialization - L.M. Bukova; I.A. Gordienko; V.F. Krovyakov; Y. I. Mironenko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: to prove the effectiveness of the use of training program aimed at improving the skill execution of tackling the ball at the opponent's shield attack in basketball specialized base preparation phase. Material: 30 sportsmen of 13-14 years old took part in the test. They were mostly from CYSS (Children and Youth Sports School). Results: low level of efficiency in the fight for the ball bounces in the attack was appeared to take place both in competitive activity in basketball and in performing the control exercises aimed to master the technique of tackling the ball. It was shown that the most important about the mastering of the technique of a rebound taking in the attack is motion. It was found that the use of simple technical actions as for the selection of the ball led to significant success in three control exercises approximately on 52.7% by improving the quality (accuracy, speed) of performing the technique mentioned in the training program. Moreover the factor of effectiveness of the fight for a ball increased on 28.9% (P <0, 05) in competitive activity. Conclusions: to recommend the use of exercises which include four possibilities of moving after being blocked by the opponent: direct output, fainted moving with further escape, turn, one step back. This is needed in order to improve the technique of taking a rebound on the shield of the opponent and also to accelerate the formation of skills formation in competitive activity.